A study of research skills of Kosovar students: An assessment of the influence of inclusion, exclusion, ethnicity, parental education and gender - Shala, Arif; Grajcevci, Albulene (Journal of Education Culture and Society, 2019)
Aim. The aim of the current study is to address a gap in literature as well as explore the factors influencing the perceptions that Kosovar students hold over their research skills. To that end, the study assessed students’ perceptions on their research abilities as well as the variables which influence these perceptions, namely inclusion, exclusion, ethnicity, gender and parental education.Methods. The study employed the quantitative research approach and 303 Kosovar university students participated in the study by answering an instrument composed of three different scales measuring the variables in the study, namely the research skills scale, inclusion scale and exclusion scale. In addition the participants answered ten demographic questions. Participation in the study was on a volunteer basis and the results were analyzed with the SPSS package.Results. Participants in this study reported the highest levels of research skills when they reported being included in academic settings. Ethnicity was a powerful influencing variable. Participants who belonged to minority groups were the ones to report the lowest levels of abilities. Contrary to existing literature, gender did not influence perceptions on abilities. Additionally, unlike in a vast number of research studies, parental education did not influence perceptions that Kosovar students held over their research skills.Conclusions. This study is the first one to research skill acquisition among student populations in Kosovo; a region that is almost absent in international literature. This research presents an overview of variables predicting perceptions held by Kosovar students on their research skills with ethnicity and inclusion being detrimental to perceptions of research skills.